SUPPORTING CREATIVITY AND TECHNOLOGICAL EDUCATION THROUGH INTERACTIVE MULTIMEDIA TOOLS - Sharipova Gulshoda Bahriddinovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores the use of interactive multimedia tools to enhance students’ creativity and technological education. The integration of multimedia in the learning process allows students to engage in hands-on activities, visualize complex concepts, and develop practical skills. The study emphasizes that interactive tools increase student motivation, foster independent learning, and strengthen both creative and technological competencies. Implementing multimedia-based strategies creates a dynamic, engaging, and effective educational environment.